2003
DOI: 10.1046/j.1478-5153.2003.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooling strategies for patients with severe cerebral insult in ICU (Part 2)

Abstract: Critically ill patients who have sustained a severe cerebral insult will be actively cooled should they develop an elevated body core temperature. Patients who require therapeutic hypothermia for neuroprotection may require the same cooling strategies. A literature review suggested limited evidence to support cooling strategies currently used within one intensive care unit. An experimental approach was used to examine the effects of paracetamol and four external cooling strategies on patients with severe cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A total of 24 original research studies evaluating fever in SAH were identified: 9 studies evaluating fever and outcome (Table 1) [1-3, 5, 9, 12-15], 12 studies evaluating temperature control strategies (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27], and 3 shivering (Table 3) [29,30]. Outcome data included 4 prospective studies, with the remainder cohort data or retrospective analyses.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 original research studies evaluating fever in SAH were identified: 9 studies evaluating fever and outcome (Table 1) [1-3, 5, 9, 12-15], 12 studies evaluating temperature control strategies (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27], and 3 shivering (Table 3) [29,30]. Outcome data included 4 prospective studies, with the remainder cohort data or retrospective analyses.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…One small study, including SAH patients, testing the efficacy of paracetamol compared with external means (fanning, evaporative cooling using cool cloths and sponging, ice packs, and cooling blanket) reported a reduction in body core temperature in 57% of patients receiving paracetamol [19]. Two other studies including SAH patients demonstrated efficacy in controlling temperature elevation with very low doses of continuously infused diclofenac [16,17].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson (1999) suggests that hyperpyrexia can be treated with anti‐pyretic drugs and notes that active cooling methods can cause shivering which increases ICP. Price et al . (2003) performed a study comparing the various methods of cooling, including paracetamol, ice packs and airflow blankets.…”
Section: Temperature Controlmentioning
confidence: 99%
“…Johnson (1999) suggests that hyperpyrexia can be treated with anti-pyretic drugs and notes that active cooling methods can cause shivering which increases ICP. Price et al (2003) performed a study comparing the various methods of cooling, including paracetamol, ice packs and airflow blankets. The small sample size meant that it is difficult to draw firm conclusions, but the researchers felt that paracetamol was an effective agent to reduce hyperpyrexia in patients with intact thermoregulatory function.…”
Section: Temperature Controlmentioning
confidence: 99%